Lactoferrin and Human Neutrophil Protein (HNP) 1–3 Levels During the Neonatal Period in Preterm Infants - Faust, Kirstin B.; Moser, Katja; Bartels, Maren; Fortmann, Ingmar; Hanke, Kathrin; Wieg, Christian; Stichtenoth, Guido; Göpel, Wolfgang; Herting, Egbert; Härtel, Christoph (Frontiers in Pediatrics, 2022)
Antimicrobial polypeptides (APPs) are part of the innate immune system, but their specific role in the context of preterm birth is not yet understood. The aim of this investigation was to determine the systemic expression of APPs, i.e. lactoferrin (LF) and human neutrophil protein (HNP) 1-3 in preterm infants in the period of highest vulnerability for infection and to correlate these biomarkers with short-term outcome. We therefore conducted a prospective two-center study including plasma samples of 278 preterm infants and 78 corresponding mothers. APP levels were analyzed on day 1, 3, 7 and 21 of life via enzyme-linked immunosorbent assay (ELISA). The levels of LF and HNP1-3 remained stable during the first 21 days of life and were not influenced by maternal levels. Elevated APP levels were found at day 1 in infants born to mothers with amniotic infection syndrome (AIS vs. no AIS, mean ± SD in ng/ml: LF 199.8 ± 300 vs. 124.1 ± 216.8, HNP 1-3 16819 ± 36124 vs. 8701 ± 11840; p=0.021, n=179). We found no elevated levels of APPs before the onset of sepsis episodes or in association with other short-term outcomes that are in part mediated by inflammation such as necrotizing enterocolitis (NEC) or retinopathy of prematurity (ROP). Interestingly, infants developing bronchopulmonary dysplasia (BPD) showed higher levels of HNP1-3 on day 21 than infants without BPD (13473 ± 16135 vs. 8388 ± 15938, n=111, p=0.008). In infants born without amniotic infection, levels of the measured APPs correlated with gestational age and birth weight. In our longitudinal study, systemic levels of LF and HNP 1-3 were not associated with postnatal infection and adverse short-term outcomes in preterm infants.